A CRITICAL DISCOURSE OF SELF-DESCRIPTION - L. I. Kirsanova (Концепт: философия, религия, культура, 2018)
The article presents the analysis of relations between the real and the imaginary. The imaginary is thought of as a broken discourse of narcissistic subject trying to conceal the horror of the real under simulacra – death of the thing, name, God. The world of the imaginary – advertising, design, theatre, cinema, etc. – allows a human to survive since simulacra and simulations inspire, excite and play with us. But it is necessary to enter the real – to restore things, not their imitations, to restore the trust to the world, to oneself. The way of returning to the subject is a critical discourse of self-description. There was a time when people were interested in the way they could meet God; today they scratch head over the manner they get caught in the lens of cameras and television. Montage, make-up, colors, peacocks, Papuans, caviar, whatever one needs for happiness is all over the world. However, in 1920s the Russian constructivism demonstrated the desire to create a minimalistic space, almost empty, bright, including minimum of things (see: Rodchenko’s “Canteen for the Workers”), to break the ground to touch the quality of things, to create a vital space for people’s trust and communication. Its followers tried to restore the broken continuity through sincerity, trust, and self-criticism, to enter the discourse of self-description. Emptiness, silence, trusts in something simple and clear open the return path back to oneself, filling with the joy of “full speech”: I am the one who speaks for myself. Finally, it’s time to live on your own.